Chaeroni , A.., Muspardi, M., Ahmed, M., Talib, K., Orhan, B. E., Lani, M. N., Asuti, Y., & Kurnaz, M. (2024). El deporte como instrumento de nacionalismo y patriotismo: una revisión sistemática de la literatura sobre el papel del deporte en la formación de la identidad nacional en diversos países (Sports as an instrument of nationalism and patriotism: a systematic literature review on the role of sports in shaping national identity in various countries). Retos, 61, 1038–1049. https://doi.org/10.47197/retos.v61.108752 - Retraction Retraction
Chaeroni , A.., Muspardi, M., Ahmed, M., Talib, K., Orhan, B. E., Lani, M. N., Asuti, Y., & Kurnaz, M. (2024). El deporte como instrumento de nacionalismo y patriotismo: una revisión sistemática de la literatura sobre el papel del deporte en la formación de la identidad nacional en diversos países (Sports as an instrument of nationalism and patriotism: a systematic literature review on the role of sports in shaping national identity in various countries). Retos, 61, 1038–1049. https://doi.org/10.47197/retos.v61.108752